Kinerja Karyawan Berdasarkan Interaksi Sosial Sebagai Variabel Mediasi Pada UMKM - Muhammad Iqbal Ramadhan; M. Nasir (POLITEKNIK LP3I JAKARTA, 2023)
In SMEs in the city of Surakarta, this study seeks to examine the relationship between dynamic competence and leadership style and employee performance, with social contact serving as a mediating variable. This study's core data came from a questionnaire that used a Likert scale as a measurement system. In this study, a non-probability sampling strategy was utilized to choose the sample. Using SmartPLS 3.0 software, 105 respondents from coffee shops in Surakarta City served as the sample for the PLS-SEM analysis. The evaluation of measurement models in the outer model and inner model serves as the study's method of data analysis. The findings revealed that: (1) employee performance was positively and significantly impacted by dynamic capability (2) Employee performance was significantly and favorably impacted by the leadership style. (3) Social interaction factors significantly and favorably impacted employee performance (4) Social contact was positively and significantly impacted by dynamic capability. (5) Social interaction is positively and significantly impacted by the element of leadership style. (6) Social interaction factors can operate as a mediator between dynamic capability factors and worker performance. (7) Social interaction factors can operate as a mediator between leadership style factors and employee performance factors.Keywords: Dynamic Capability, Employee Performance, Leadership Style, Social Interaction.